Cybernotopics and lineaments - Gaevskaya, Zlata (project baikal, 2025)
It is necessary to turn from the planar chain characteristics of the surface and the static a priori placement of people and objects in space to cybernotopic codes for constructing space as a cast of the hidden stress-strain state of the Earth. Landscape possibilities of space should be considered through the prism of the unity of spatial bodies, forms, functions and meanings based on the patterns of spatial self-organization. The cybernotopic vision of space implies understanding that it has grown naturally out of the past and reflects the perception of the Earth as a complex organism. Cybernotopic space can be studied using lineaments reflecting a single fractal system for the Earth
Keywords: theory; cybernotopics; nonlinearity; fractal-wave system; lineaments; space; place